Floral biology of Scaphochlamys (Zingiberaceae) focusing on Bornean taxa. Issue 1 (10th October 2019) - Ooi, Im‐Hin; Wong, Sin‐Yeng
Abstract : An overview of the floral biology including floral odour analyses of twenty‐two Bornean Scaphochlamys taxa and three ex Bornean Scaphochlamys taxa was undertaken. All Scaphochlamys species investigated bloom diurnally. Pollen is released gradually, either simultaneously with stigma secretion or later (mostly within one hour). Flowers of most Scaphochlamys species were found to emit a mild odour but a few are odourless. Stigmas and anther spurs (where present) differ among the taxa investigated. Natural fruit set percentages of all species investigated were very low, up to 14.29%. Scaphochlamys species are facultatively xenogamic as the pollen/ovule ratios (P/O ratios) were high. Analysis of floral odour revealed 102 identifiable floral volatile organic compounds (VOCs), representing 31.8% of the compounds found. The volatile fraction was characterized by the aliphatics class (21.5%), monoterpenes (3.4%), irregular terpenes (0.3%) and benzenoids and phenyl propanoids (0.6%). Two pollinator guilds were found: halictid bees and Amegilla bees.